(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
This study aims to analyze mental and perceptional factors influencing on customer satisfaction and its role on word-of-mouth with regard to the mediating role of customer commitment. Statistical universe of the study is generally customers of sales web sites. Since statistical universe of this research is unlimited, it’s been used convenience sampling method. To collect data, the questionnaire was used and was distributed in the volume via Telegram application. To analyze the collected data, SmartPLS Ver.3 was used and structural equations modelling (SEM) was employed. Results showed that factors of entertainment, perceived justice and subjective norms have a positive impact on customer satisfaction, whereas no significant relationship was found between perceived effort and customer satisfaction. Further, customer commitment mediates the relationship between customer satisfaction and WOM.